2020
DOI: 10.1186/s12889-020-08766-7
|View full text |Cite
|
Sign up to set email alerts
|

‘The public health turn on violence against women’: analysing Swedish healthcare law, public health and gender-equality policies

Abstract: This article focuses on policy and law concerning violence against women as a public health issue. In Sweden, violence against women is recently recognized as a public health problem; we label this shift "The public health turn on violence against women". The new framing implies increased demands on the Swedish healthcare sector and its' ability to recognise violence and deal with it in terms of prevention and interventions. The aim was to describe and discuss the main content and characteristics of Swedish he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…The present study was conducted as an exploratory research with two objectives: (1) to analyze how attraction to violent masculinities showed in the context of the peer group can influence toxic relationships among adolescents, and (2) to analyze the preventive impact of knowing the harmful effects of toxic relationships and violent masculinities on health.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study was conducted as an exploratory research with two objectives: (1) to analyze how attraction to violent masculinities showed in the context of the peer group can influence toxic relationships among adolescents, and (2) to analyze the preventive impact of knowing the harmful effects of toxic relationships and violent masculinities on health.…”
Section: Methodsmentioning
confidence: 99%
“…Increasingly younger women and girls are experiencing this reality. Due to the devastating effects of violence against women on women's health, it is increasingly being considered a public health issue [1].…”
Section: Introductionmentioning
confidence: 99%
“…While disclosure can be a door opener to support, publicising it as ‘the solution’ risks minimising the reality that, after disclosing, there may still be a long way ahead for women. The criticism has also been made that the focus on disclosure risks positioning it as a measure of success, disregarding the fact that success is dependent on what comes after women disclose and that unfortunately what comes after disclosure is not always what women require [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…In most countries around the world, GBV has shifted from being mainly addressed by feminist civil society organisations to becoming recognised as a social problem for which the welfare system has a major responsibility [ 4 ]. In Spain, the 2004 Law on Protective Measures against Gender-based Violence details the responsibilities of different sectors, including social services, educational and legal systems, and healthcare services.…”
Section: Introductionmentioning
confidence: 99%
“…A public health approach to violence against women complements the human rights approach in that it employs a science-driven, population based, interdisciplinary and intersectoral approach to prevent violence against women, focusing on the prevention of violence before it occurs. 9 , 10 A public health perspective on violence against women thus seeks to address the societal and community factors that lead to these forms of violence, including the perpetuation of beliefs within society that condone violence. 11 The Court identified that sexual harassment in school contexts in Ecuador has been on the rise since 1998.…”
Section: The Judgment’s Impact On Public Health and Educationmentioning
confidence: 99%